INVESTIGATION OF THE EFFECT OF THE DISCONTINUITY DIRECTION ON FLUID FLOW IN POROUS ROCK MASSES ON A LARGE-SCALE USING HYBRID FVM-DFN AND STREAMLINE SIMULATION - Sajad Namdari; Alireza Baghbanan; Hamid Hashemolhosseini (Rudarsko-geološko-naftni Zbornik, 2021)
Understanding the fluid behaviour in rock masses is of great importance in various rock mass-related engineering projects, such as seepage in tunnels, geothermal reservoirs, and hazardous waste disposal. Different approaches have been implemented to study the flow pattern in fractured porous rock masses. Laboratory experiments can provide good information regarding this issue, but high expenses aside, they are time-consuming and suffer the lack of ability to study field scale mediums. Numerical methods are beneficial in simulating such mediums with the Discrete Fracture Network (DFN) method in terms of costs and time as they offer sufficient flexibility and creativity. In this paper, a Matlab code was extended to study the flow regime in a Dual Permeability Media (DPM) with two point sources in the right and left side of the model as an injector and a producer well, respectively. A high permeability discontinuity with different angles was embedded in a very low-permeability limestone matrix. Pressure equations were solved implicitly with a two-point flux approximation scheme of the Finite Volume Method (FVM). Streamlines were traced in the medium and used to analyse the model’s hydraulic behaviour with the aid of Time Of Flight (TOF) for each point. The results show that the FVM-DFN hybrid method can be used as a fast method for fluid flow in DPM with the aid of streamline simulation to study the fluid flow in a large model with discontinuity.